Diagnostic validity of the use of questionnaires, clinical examination and a portable single-channel electromyography device for Sleep Bruxism - Barbosa, Juliana Stuginski (2015)
The presented study intended to compare two methods for assessing Sleep Bruxism (SB): International Classification of Sleep Disorders diagnostic criteria (ICSD-3) and a portable single-channel electromyography (EMG) device (Grindcare) with gold standard polysomnographic (PSG) examination. The comparison with PSG was used to determine an appropriate cut-off value and the number of nights of sleep with the Grindcare device necessary for a valid/reliable SB diagnosis. Twenty consecutive post-graduate students and staff at Bauru School of Dentistry composed the sample. Each participant underwent interview, clinical assessment, the Grindcare for five consecutive nights and a PSG exam. The discrimination between bruxers and non-bruxers was based only on the PSG analysis. Data about electromyography per hour with Grindcare (EMG/h) and PSG (bursts/h) were scored. The validity of ICSD-3 criteria and the Grindcare device were assessed by using receiver operating characteristics (ROC) curve analysis (AUC), likelihood ratios (LR), the diagnostic odds ratio (DOR) and Bland-Altman analysis. The ICSD-3 diagnostic criteria items for SB had fair to moderate concordance with PSG diagnosis, with AUC ranging from 0.55 to 0.75. The best value of agreement was obtained by the report of SB more than once a week associated with a report of transient morning jaw muscle pain or fatigue with a moderate, but significant agreement with the PSG SB diagnosis (AUC=0.75) with 90% specificity, positive LR=6 and DOR=13.5. When the frequency of self-reported SB increased to more than 4 times per week, the combination of this finding with tooth wear had also high values of agreement with PSG SB diagnosis (AUC= 0.75, LR=6, DOR=13.6). Bland-Altman analysis of the EMG bursts/h showed positive agreement between Grindcare device and PSG exam. The ROC analyses also showed that using a minimum of 18 EMG/h for 3 nights and 19 EMG/h for 5 nights in Grindcare as cut-offs resulted in a 90% specificity and positive LR equal to 5. Since there is considerable heterogeneity in the results, the application of ICSD-3 for SB clinical diagnosis may be limited. Moreover, the Grindcare is able to predict SB diagnosed by PSG with a reasonable accuracy, when used for 3 or 5 consecutives nights, and it may be a valid choice in clinical practice for SB assessment.